Congestion control and fairness with dynamic priority for ad hoc networks. (2018) - Mishra, Tapas Kumar; Tripathi, Sachin
Recently, the network structure has changed rapidly in modern applications and has imposed priority for heterogeneous applications. In some scenarios, the priorities of the flows need to change in the middle of the communication. However, the major problem is that the packets of different applications are not served at the destination by their expected priority ratio even if the priority does not change. Considering the above problem, this paper presents a fair packet scheduling policy which collects information from each individual flow according to its priority and auto-updates the priorities of flows when required. Moreover, a hybrid congestion control technique based on queue occupancy and channel utilisation is framed to control congestion. The proposed model has been simulated using NS2 for two applications. The simulation result shows the model performs better with respect to fairness among different applications. Moreover, it achieves improved throughput by reducing packet loss.